The impact of technology on employment: a research agenda for New Zealand and beyond. (3rd July 2018) - Halteh, Jane; Arrowsmith, Jim; Parker, Jane; Zorn, Theodore E.; Bentley, Tim
ABSTRACT: The rapid development and systemic integration of new technologies has reignited concerns about the implications of automation for the volume and quality of jobs. However, there is surprisingly little empirical work that explores the drivers, constraints and employment impacts of technology from a business perspective across different sectors. This research note briefly interrogates the relevant literature, with particular regard to the New Zealand context, and argues the case for multi-sector, longitudinal research.